Prototype Sensor Gesture untuk Monitoring Pengunjung dan Sensor Asap pada Smoking Room di Gedung Serbaguna - Nina Paramytha; Muhammad Hanif (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
This project aims to design and develop a prototype system based on gesture sensors to monitor visitors and smoke sensors to detect the presence of smoke in designated smoking rooms. The system is designed to enhance comfort, safety, and operational efficiency in multipurpose buildings. Utilizing the Arduino Uno microcontroller, the device is equipped with various components, such as a gesture sensor to detect visitor movements entering and exiting the building, enabling visitor monitoring for resource allocation. Meanwhile, the smoke sensor is designed to identify and monitor smoke concentration in the smoking room to prevent the spread of smoke to other areas.The device also includes additional features, such as an automatic exhaust fan and an LCD display for process monitoring. Test results show that the developed prototype has a high accuracy rate in detecting visitor gestures and can reliably and quickly detect the presence of smoke. This system provides an innovative solution to support smarter, safer, and more eco-friendly management of multipurpose buildings. This research is expected to serve as a foundation for further advancements in the application of sensor technology in public facilities.